Hedging Ratio Measurement Methods and Hedging Effectiveness in Jakarta Futures Exchanges - Wibowo, Buddi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
Estimation method ofÂ  hedge ratio is a crucial step in hedging strategies in the commodity futures market. This study examines the effectiveness of hedging strategy against cash position in Indonesiaâs cocoa beans and Robusta coffee spot market using three hedge ratio estimation methods: OLS, Vector Error Correction Model, and Threshold-ARCH. The results show the hedging effectiveness in the Jakarta Futures Exchange is considerably highly effective to reduce the impact of fluctuations of spot price. The effectiveness of hedging strategy using Â OLS as theÂ  simplest method is close to VECM method and TARCH. Implementation OLS hedge ratio resultedÂ  the highest hedging Â effectiveness and give a strong support for market players in executing a hedging strategy in Jakarta Futures Exchange due to OLS Â simplicity in estimation procedure